When Right Makes Might Rising Powers and World Order - Stacie, Goddard (Cornell University Press, 2018)
Why do great powers accommodate the rise of some challengers, while others are contained and confronted, even at the risk of war? The book proposes that when faced with a new challenger, great powers will attempt to divine its intentions, to determine whether that rising power poses a revolutionary threat to the system, or whether it can be incorporated into the existing international order. In departing from conventional rationalist and realist theories of international relations, the author argues that established powers come to understand a rising power's intentions by observing how it justifies its behavior through diplomacy and its claims on the way it exerts its power. Diplomatic rhetoric, therefore, plays a critical role in the formation of grand strategy. Legitimacy is not marginal to international relations; it is essential to the practice of power politics.